Encapsulating access to heterogeneous databases using JavaBeans - 428890 Rosely Kumoi (Heriot-Watt : Heriot-Watt University, 1998)
Thesis (MSc in Distributed and Multimedia Information Systems) - Heriot-Watt University, 1998